Chewing Entrains Cyclical Actions but Interferes With Discrete Actions in Children. Issue 3 (4th May 2021) - Prebor, Jessica; Samulski, Brittany; Armitano-Lago, Cortney; Morrison, Steven
Abstract: Functional chewing patterns are achieved early in life prior to other motor skills like walking. Chewing seems to improve specific aspects of attention; however, there is limited research on chewing in dual motor tasks. This study examined relationships between chewing and secondary motor tasks in children. Sixteen typically developing children (13.1 ± 2.3 years) participated in finger tapping, simple reaction time, and walking while chewing at different speeds. The chewing rates varied when produced with a secondary motor task, especially for slow chewing and preferred chewing, and the secondary motor tasks were differentially influenced by the chewing. This relationship was not as strong as what has been reported in adults. It appears the neural oscillatory mechanisms involved in chewing and the secondary motor tasks may not be fully developed in children.